2004
DOI: 10.1038/modpathol.3800207
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite instability in gastric MALT lymphoma

Abstract: The role of microsatellite instability and defects in DNA mismatch repair mechanism in the pathogenesis of gastric lymphoma of mucosa-associated lymphoid tissue (MALT) type is still controversial, as both negative and positive findings have been reported. This may be explained mainly by arbitrary selection of the tested loci, the use of various techniques of microsatellite instability analysis and by different definitions of replication error positive phenotype. The aim of our study was to evaluate the instabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…Obviously, microsatellite instability and defects in DNA mismatch repair mechanism are also involved in the pathogenesis of gastric MALT lymphoma. Nine of 13 patients with gastric MALT lymphoma (69%) revealed microsatellite instability [18]. Seven of them had replication‐error‐positive phenotype.…”
Section: H Pylori and Gastric Malt Lymphomamentioning
confidence: 99%
“…Obviously, microsatellite instability and defects in DNA mismatch repair mechanism are also involved in the pathogenesis of gastric MALT lymphoma. Nine of 13 patients with gastric MALT lymphoma (69%) revealed microsatellite instability [18]. Seven of them had replication‐error‐positive phenotype.…”
Section: H Pylori and Gastric Malt Lymphomamentioning
confidence: 99%
“…For the first time, this study established a MSI-positive Burkitt's lymphoma cell line NAMALWA, capable of correcting base-base alterations and/or insertion-deletion loops with high efficacy despite faulty DNA MMR system [19]. Studies on patient samples showed an increased frequency of loss of expression in MSH2 and MLH1 genes by immunohistochemical staining, indicating the presence of MSI in chronic B cell lymphocytic leukemia [20]. All of the above experiments show the dynamism of cancers and compel us to consider MSI as a part of hematologic malignancies.…”
Section: Microsatellite Instability In Hematologic Malignanciesa Diffmentioning
confidence: 96%
“…Certain genetic aberration were found to be associated with gastric MALT lymphoma including trisomy 3, trisomy 5, trisomy 18, t [11,18] (q21,q21) as well as mutation in p53 and p16 which are linked to DLBCL [3,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Microsatellites are short repeat sequences dispersed throughout the genome. Defects in the DNA repair are reflected by DNA microsatellite instability [18]. Microsatellite instability is used to identify genetic loci that have been lost to detect genomic alterations and to evaluate the contribution of the mutator pathway to the gastric lymphoma pathogenesis [3,18].…”
Section: Introductionmentioning
confidence: 99%